Author Correction: Investigating the nature of active forces in tissues reveals how contractile cells can form extensile monolayers (Nature Materials, (2021), 20, 8, (1156-1166), 10.1038/s41563-021-00919-2) - Balasubramaniam, Lakshmi; Doostmohammadi, Amin; Saw, Thuan Beng; Narayana, Gautham Hari Narayana Sankara; Mueller, Romain; Dang, Tien; Thomas, Minnah; Gupta, Shafali; Sonam, Surabhi; Yap, Alpha S.; Toyama, Yusuke; Mège, René Marc; et al. (Nature Materials, 2021)
In the version of this Article originally published, the captions for Extended Data Figs. 1, 2 and 3 were in the wrong order and did not correspond to their associated figures. The correct captions are listed below and the Article has been corrected accordingly. In addition, the cell line MCF7 was mistakenly written as ‘MCF7A’ in seven instances in the main text, Methods and Extended Data Fig. 4 caption, and as ‘MCF10A’ in one instance in the ‘Author contributions’ section; these errors have now been corrected.
CRIS-Team Scopus Importer:2024-02-19